Psychometric Properties for the Arabic Version of Personality Inventory for DSM-5 "PID-5" in Non-Clinical Individuals - Elsayed, Hala Abd Ellatif (جامعة سوهاج - كلية التربية, 2021)
تم استخدام النموذج القائم على الأبعاد كنموذج بديل لاختبارات تشخيص اضطرابات الشخصية في الدليل التشخيصي والإحصائي للاضطرابات العقلية - الإصدار الخامس (5-DSM)؛ الجمعية الأمريكية للطب النفسي (APA، 2013). ويتضمن هذا النموذج تقييم أداء الشخصية المرضية (المعيار أ) وسمات الشخصية التكيفية (المعيار ب). وقد تم بناء قائمة الشخصية من قبل فريق عمل من المختصين التابع للدليل التشخيصي والإحصائي الخامس وذلك من أجل تقييم سمات الشخصية المرضية وفقا لنموذج الأبعاد كأداة أبعاد جديدة تتكون من 220 فقرة متضمنة في 25 جانبا يميز خمسة أبعاد لاضطرابات الشخصية. وركزت الدراسة الحالية على الخصائص السيكومترية لـ 5-PID في العينة غير السريرية، وفي دراسة مستعرضة، تمت الترجمة العربية لـ 5-PID وتم تطبيقه على 537 طالبا جامعيا في جامعة قناة السويس. بعد جمع البيانات، تم التحقق من ثبات قائمة الشخصية باستخدام طرق الاتساق الداخلي وطريقة إعادة الاختبار. وتم التحقق من الصدق البنائي ل 5-PID باستخدام التحليل العاملي التوكيدي. بالإضافة إلى ذلك، تم استخدام طرق الصدق التقاربي لتقييم صدق قائمة الشخصية -5 PlD. أظهرت النتائج معاملات اتساق داخلية مرتفعة للأبعاد والأوجه. بالإضافة إلى ذلك، تشير معاملات إعادة الاختبار والاختبار (حتى 0.70) إلى ثبات القائمة، وكان الصدق التقاربي للقائمة مع مقياس NEO—FFI مناسبا. دعمت نتائج الدراسة الخصائص السيكومترية للنسخة العربية من 5-PID في المجموعات غير السريرية.
An alternative dimensional model to test and diagnose personality disorders is used in the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition (DSM-5; American Psychiatric Association [APA], 2013). This model includes assessment of impaired personality functioning (Criterion A) and Adaptive Personality Traits (Criterion B). The DSM-5 Personality and personality disorders workgroup developed the personality inventory for DSM-5 (PID-5) to assess the pathological personality traits within this new model as a new dimensional tool consisting of 220 sentences overarch into 25 facets that distinguish five higher order domains of clinically important personality disorders and was developed to operationalize the pathological personality disorders. The current study focused on the psychometric properties of PID-5 in non-clinical sample. In a cross-sectional study, the Arabic translation of the PID-5 was administered to 537 university students at Suez Canal University (83.05% female and 16.95% male, mean age = 19.8 years, SD = 3.9). After data collection, the reliability of the inventory was investigated using internal consistency, test-retest methods. The facet structure was examined using structural equation modeling (SEM). In addition, convergent validity methods were used to evaluate the validity of the scale. The results showed adequate internal consistency coefficients for domains and facets. In addition, the test-retest coefficients (up to 0.70) suggested scale stability. The convergent validity of the inventory with the NEO-FFI scale was appropriate. The results of the study supported the psychometric properties of the Arabic version of PID-5 in non-clinical populations.
Keywords: علم النفس الإكلينيكي -- الاضطرابات العقلية -- اضطرابات الشخصية -- الخصائص السيكومترية